CUT homeobox genes: transcriptional regulation of neuronal specification and beyond - Leyva-Díaz, Eduardo (Frontiers in Cellular Neuroscience, 2023)
CUT homeobox genes represent a captivating gene class fulfilling critical functions in the development and maintenance of multiple cell types across a wide range of organisms. They belong to the larger group of homeobox genes, which encode transcription factors responsible for regulating gene expression patterns during development. CUT homeobox genes exhibit two distinct and conserved DNA binding domains, a homeodomain accompanied by one or more CUT domains. Numerous studies have shown the involvement of CUT homeobox genes in diverse developmental processes such as body axis formation, organogenesis, tissue patterning and neuronal specification. They govern these processes by exerting control over gene expression through their transcriptional regulatory activities, which they accomplish by a combination of classic and unconventional interactions with the DNA. Intriguingly, apart from their roles as transcriptional regulators, they also serve as accessory factors in DNA repair pathways through protein-protein interactions. They are highly conserved across species, highlighting their fundamental importance in developmental biology. Remarkably, evolutionary analysis has revealed that CUT homeobox genes have experienced a remarkable degree of rearrangements and diversification compared to other classes of homeobox genes, including the emergence of a novel gene family in vertebrates. Investigating the functions and regulatory networks of CUT homeobox genes provides significant understanding into the molecular mechanisms underlying embryonic development and tissue homeostasis. Furthermore, aberrant expression or mutations in CUT homeobox genes have been associated with various human diseases, highlighting their relevance beyond developmental processes. This review will overview the well known roles of CUT homeobox genes in nervous system development, as well as their functions in other tissues across phylogeny.